Contribution of GalU to biofilm formation, motility, antibiotic and serum resistance, and pathogenicity of Salmonella Typhimurium - Guo, Lili; Dai, Huilin; Feng, Saixiang; Zhao, Yongda (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Salmonella Typhimurium is the leading cause of foodborne illnesses in China, resulting in major epidemics and economic losses in recent years. Uridine diphosphate–glucose pyrophosphorylase galU plays an important role in thebiosynthesis of the bacterial envelope. Herein, we evaluated the role of galU in S. Typhimurium infection in chicken. Methods A galU gene mutant was successfully constructed by red homologous recombination technology, and biological characteristics were studied. Results The galU mutant strain had a rough phenotype;was defective in biofilm formation, autoagglutination, and motility; exhibited greater sensitivity to most antibiotics, serum, and egg albumen; and had lowercapacity for adhesion to chicken embryo fibroblasts cell line (DF-1). The galU mutant showed dramatically attenuated pathogenicity in chicken embryos (100,000-fold), BALB/c mice (420-fold), and chicks (100-fold). Discussion The results imply that galU is an important virulence factor in the pathogenicity of S. Typhimurium, and it may serve a target for the development of veterinary drugs, providing a theoretical basis for the prevention and control of S. Typhimurium.